(3eQGbHI GdJSjjQ hGdCOGA aj GdeDSSI GdGbJUGOjI (B:s (3GdeDSSI GdYehejI HGdLRGFQ (B/s - (3YOhf, fGUQ OGOjs; (3GdhGMO, YHO Gddg bhjOQs ((3GdLRGFQ(B: s (3OGQ GdeMeOjI GdYGeI(B, s)
(3jVe eaGgje YGeI Mhd JMSjf GdCOGA aj GdeDSSI, eONd dfXGe eQGbHI GdJSjjQ HGdeDSSI, CgOGa eQGbHI GdJSjjQ hYdGbJg HfXGe GdeYdheGJ, ehbY fXGe eQGbHI GdJSjjQ heQGMd Yedg, hGbY COGA GdeDSSI GdYehejI hJWhQgG aj GdLRGFQ, GdCOhGJ GdcejI GdcdGSjcjI eMGSHI GdJcGdja, GdehGRfI GdJbOjQjI hGdJMdjd GdeGdj, GdCOhGJ GdcejI GdMOjKI heMGSHI GdJcGdja Ydi CSGS GdGfTWI dhMGJ GdbjGOI, GdbjGS GdebGQf hEYGOI GdgfOSI hdhMI GdbjGOI GdeJhGRfI, GdCOhGJ GdcjajI deQGbHI GdJSjjQ hOhQgG aj GdCOGA KbGaI GdeDSSI GdejRGfjI GdGLJeGYjI(B.s
Keywords: (3GdQbGHI GdEOGQjIs; (3GdeDSSGJ GdEfJGLjI s; (3Jbjje GdCOGAs